ENTREPRENEURSHIP DEVELOPMENT, BUSINESS FINANCING AND WOMEN’S ECONOMIC EMPOWERMENT IN EKITI STATE, NIGERIA - Joseph Ojo, Ekiran (International Journal of Social Science, 2025)
Nigerian population in 2022 was 218.54 million and women population out of the statistics was 108.9 million, representing 49.46% of the total population. Literature confirms that entrepreneurship has been conceptualized as the engine of economic growth both in developed and less developed countries. Based on these facts, this research work aims at evaluating the effects of entrepreneurship development and business financing on women’s empowerment in Ekiti State. The study uses descriptive statistics method of data analysis to carry out the objectives of the research project. The outcomes of the research findings confirmed that women’s engagement in entrepreneurship projects such as restaurant services, meat retailing, barbing and hair weaving promote women’s economic status to finance their children education, pay tax to support infrastructure development and reduce poverty level of citizens. The study appealed to government to organize training programmes on the government’s proposal for women capacity building for economic self reliance and provide the women with soft loans with flexible repayment schedules in the process of entrepreneurship development in Ekiti State, Nigeria